International scientific conference proceedings Enhancing Cooperation to Promote Sustainable Tourism in Respone to Climate Change, the Fourth Industrial Revolution and Artifical Intelligence (Đại học Cần Thơ, 2024)
International scientific conference "Enhancing Cooperation to Promote Sustainable Tourism in Respone to Climate Change, the Fourth Industrial Revolution and Artifical Intelligence" is a forum for experts, scientics and interested people to dicuss, share knowledge and propose solutions to promote forms of connection and cooperation, sustainable tourism development, improving the adapt to climate change.